Waterproof breathable anti-mildew bamboo-cotton composite fabric fitted cover

By using a combination technology of bamboo cotton blended base layer, nano-silver antibacterial finishing agent and nano-cellulose fiber dispersion in the cover fabric, the existing cover fabric has been solved, and the waterproof, breathable and mildew resistance performance is insufficient, achieving efficient waterproof, breathable and mildew resistance effects, improving the overall quality and service life of the cover.

CN119856853APending Publication Date: 2025-04-22YIXING HONGYE TEXTILE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411876463.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The existing bed cover fabric has shortcomings in waterproofing and breathability, which is difficult to meet consumers' needs for comfort, health and versatility. At the same time, the anti-mold effect will gradually weaken after the number of washings increases.

Method used

The bamboo cotton blended base layer is used, combined with nano-silver antibacterial finishing agent and nano-cellulose fiber dispersion, to form an intermediate layer and surface layer, enhance structural stability, and improve the anti-slip performance of the bed cover through an elastic anti-slip cloth.

Benefits of technology

It realizes the waterproof, breathable and anti-mold properties of the bed cover, improves the overall quality and service life of the bed cover, and ensures the health and comfort of the skin.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119856853A_ABST
    Figure CN119856853A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of fitted cover fabric preparation, in particular to a waterproof breathable anti-mildew bamboo-cotton composite fabric fitted cover which comprises a fitted cover face, a surrounding edge connected with the periphery of the fitted cover face and elastic anti-skid cloth arranged at the bottom of the surrounding edge. The bamboo hat face comprises a bamboo-cotton blended base layer, a middle layer arranged on the bamboo-cotton blended base layer and a surface layer arranged on the middle layer. Bamboo fibers and cotton fibers in the bamboo-cotton blended base layer are blended, and the gray fabric is treated through the nano-silver antibacterial finishing agent, so that the antibacterial ability of the gray fabric is improved, and the air permeability of the gray fabric can be guaranteed; the nano cellulose fibers and the sodium carboxymethyl cellulose are dispersed in the N, N-dimethylformamide, the PU resin and the N, N-dimethylformamide are mixed according to a certain proportion, and the formed middle layer can enhance the structural stability and has positive effects on the waterproof performance, the air permeability, the mildew resistance and the like of the fitted cover.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of preparation of fitted sheet fabrics, and in particular to a waterproof, breathable, mildew-resistant bamboo-cotton composite fabric fitted sheet. Background Art

[0002] Bamboo fiber and cotton fiber are both popular materials for bedding fabrics. In daily life, bed sheets are often at risk of contamination by various liquids. People may accidentally spill drinks on the bed, or sweat a lot during sleep, and the sweat will penetrate into the bed sheet. If the bed sheet is not waterproof, these liquids can easily penetrate into the mattress, which will not only stain the mattress, but also easily breed bacteria and produce odors, shortening the life of the mattress. Therefore, waterproof performance is essential to keep the bed clean and hygienic. In addition, the good breathability of the bed sheet can keep the skin dry and help improve sleep quality, which is especially important for some people with sensitive skin.

[0003] During the use of the fitted sheet, it is inevitable that it will come into contact with various microbial sources, such as mold spores in the air and microorganisms on human skin. If the fitted sheet is kept damp for a long time, especially when the air permeability is poor, it provides an ideal breeding ground for mold growth. Mold growth will not only damage the appearance of the fitted sheet, causing unsightly mold spots, but also decompose the cellulose and other components in the fabric, reducing the strength and service life of the fabric.

[0004] Although traditional bamboo cotton fabrics have certain air permeability and antibacterial properties, their waterproof properties are often poor. Purely waterproof fabrics may have the problem of insufficient air permeability and cannot meet consumers' demands for comfortable, healthy and multifunctional mattress covers. The existing antibacterial mattress covers will gradually lose their anti-mildew effect as the number of washings increases. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a waterproof, breathable, mildew-resistant bamboo-cotton composite fabric fitted sheet.

[0006] The technical solution of the present invention is: a waterproof, breathable, mildew-resistant bamboo-cotton composite fabric mattress cover, comprising a mattress cover surface, a surrounding edge connected to the mattress cover surface, and an elastic anti-slip cloth arranged at the bottom of the surrounding edge; the mattress cover surface comprises a bamboo-cotton blended base layer, an intermediate layer arranged on the bamboo-cotton blended base layer, and a surface layer arranged on the intermediate layer.

[0007] Description: Bamboo fiber has good air permeability. There are many hollow structures inside its fibers, which allow air to flow freely. At the same time, cotton fiber is a natural skin-friendly fiber. After the two are blended, the mattress cover is more skin-friendly.

[0008] Cotton fiber itself has good moisture absorption capacity and can absorb sweat discharged from the human body. Bamboo fiber also has certain moisture absorption and release characteristics. The base layer after the two are blended can quickly absorb and release moisture to keep the sleeping environment dry. The middle layer can be used to connect the bamboo-cotton blended base layer and the surface layer, enhance the structural stability of the entire mattress cover, and also improve the waterproof and breathable effect of the mattress cover. The surrounding edge connects the surrounding of the mattress cover to form a complete mattress cover shape, which can wrap the edge of the mattress. The elastic anti-slip cloth is set at the bottom of the surrounding edge. It can use its own elasticity to fit tightly on the mattress to prevent the mattress cover from sliding and shifting during use, ensuring that the mattress cover is always in the correct position and improving the convenience of use.

[0009] Furthermore, the preparation method of the bamboo-cotton blended base layer is: bamboo fiber and cotton fiber are selected to be blended into a grey cloth according to a blending ratio of 3 to 4:6, and then the grey cloth is immersed in a nano-silver antibacterial finishing agent with a concentration of 3 to 5 g / L, the particle size of the nano-silver is controlled at 20 to 50 nm, and then the cloth is squeezed and dried, the squeezing rate is 70 to 80%, and the drying temperature is 50 to 70°C; the length of the bamboo fiber is 38 to 42 mm, and the fineness is 1.6 to 1.8 dtex; the cotton fiber is long-staple cotton, the cotton fiber length is 35 to 40 mm, and the micronaire value is 3.7 to 4.2.

[0010] Description: The cotton fiber ratio is relatively high, which can lay a soft and comfortable foundation for the fitted sheet. The bamboo fiber length is 38-42mm and the fineness is 1.6-1.8dtex, which allows it to be evenly distributed when blended to ensure a uniform fabric structure. The good air permeability of bamboo fiber allows air to circulate smoothly in the fitted sheet, and its own antibacterial properties help reduce bacterial growth. The cotton fiber is long-staple cotton with a fiber length of 35-40mm and a micronaire value of 3.7-4.2. The longer fibers of long-staple cotton can enhance the strength and durability of the fabric. The appropriate micronaire value indicates that it is mature and has good hygroscopicity, which can quickly absorb moisture such as human sweat. , keep the fitted sheet dry, immerse the grey fabric in an antibacterial finishing agent with a concentration of 3-5g / L and a nanosilver particle size of 20-50nm. Nanosilver can effectively inhibit the growth and reproduction of a variety of bacteria, greatly reducing the risk of health problems caused by bacterial growth, especially for those with sensitive skin. During the treatment process, the liquid rolling rate is 70-80% to ensure that the antibacterial finishing agent is evenly distributed on the grey fabric, avoiding insufficient coverage caused by too low a liquid rolling rate or waste caused by too high a liquid rolling rate and affecting subsequent treatment. The drying temperature of 50-70℃ can effectively fix the antibacterial finishing agent without damaging the grey fabric fiber structure due to excessively high temperature, thereby maintaining the good performance of the fitted sheet.

[0011] Furthermore, the preparation method of the intermediate layer is as follows: by mass percentage, 0.5-5% of nanocellulose fibers and 0.01-0.2% of sodium carboxymethyl cellulose are dispersed in the remaining N,N-dimethylformamide, and stirred evenly to obtain a nanocellulose fiber dispersion; at the same time, N,N-dimethylformamide is weighed separately, and PU resin and N,N-dimethylformamide are mixed and dissolved in a mass ratio of 1:4-10 to obtain a PU resin solution; the nanocellulose fiber dispersion is added to the PU resin solution and stirred for 2-4 hours, the mixing mass ratio of the nanocellulose dispersion and the PU resin solution is 1:3-6, and the stirring speed is 500-1000rpm to obtain a uniformly dispersed blended solution; then the blended solution is coated on the bamboo-cotton blended base layer with a coating thickness of 0.05-0.1mm, and the vacuum degree is controlled to be -0.05-0.1MPa at a temperature of 25-40°C until the solvent evaporates and forms a film to obtain the intermediate layer.

[0012] Description: Nanocellulose fibers have good mechanical properties, can enhance the overall strength of the middle layer, retain the breathable structure in the membrane, help maintain the structural stability of the fitted sheet, and make the fitted sheet more durable in daily use; sodium carboxymethyl cellulose acts as a dispersant in this process, which can ensure that the nanocellulose fibers are evenly dispersed and prevent them from agglomerating. Evenly dispersed nanocellulose fibers can avoid forming weak points or blocking channels in the middle layer, thereby ensuring the consistency of the performance of the middle layer; the blended solution is coated on the cotton blended base layer, and the appropriate coating thickness can ensure that the middle layer can exert its waterproof and breathable properties without making the fitted sheet too thick to affect its softness and comfort; the solvent is evaporated to form a film at a temperature of 25-40°C and within a specific vacuum range. Under mild conditions, the formed film can be ensured to have stable quality and uniform structure. This uniform middle layer membrane structure helps to achieve the waterproof, breathable and mildew-resistant performance requirements of the fitted sheet, and improve the overall quality of the fitted sheet.

[0013] Furthermore, the nanocellulose fiber is one of CNF, CNC and BNC.

[0014] Description: CNF has a high aspect ratio and a unique network structure. Its slender fiber morphology can form a complex microstructure in the composite membrane. This structure helps to regulate the transmission path of gas and water molecules. In the composite membrane, the CNF network can construct tiny pores. These pores are small enough to prevent the penetration of liquid water. According to the principle of capillary action, when the pores are smaller than a certain size, liquid water cannot pass through, thereby achieving a waterproof effect. At the same time, these pores can allow gas molecules such as air and water vapor to pass freely to achieve the purpose of breathability; CNC is a highly crystallized rod-like structure with good rigidity. In the composite membrane, CNC can play a role similar to a skeleton; when compounded with PU, CNC can be arranged in an orderly manner in the membrane. This orderly arrangement can limit the entry of liquid water to a certain extent. At the same time, since there are certain gaps between CNCs, these gaps can allow gas molecules to pass through, which helps to achieve the function of breathable and waterproof. BNC has high purity, high crystallinity and a unique three-dimensional network structure. This three-dimensional network structure is interwoven by nano-scale fibers and is very regular. When it is compounded with PU to form a membrane, the three-dimensional network structure of BNC can provide an effective barrier to prevent the intrusion of liquid water, and the network formed by the interweaving of nano-scale fibers has channels for gas molecules to diffuse, thereby achieving a breathable and waterproof effect.

[0015] Furthermore, the preparation method of the surface layer is: PLON polylactic acid fibers are selected and opened into loose bundles, and then the opened fibers are combed into single fibers by a carding machine and arranged in a directional manner into a web, and the surface density is controlled to 10 to 50 g / m by adjusting the roller speed and the gauge. 2 , obtain a fiber mesh, lay the fiber mesh on the middle layer, apply a pressure of 0.5 to 2 MPa to the fiber mesh for 10 to 30 seconds using a hot press machine, and the hot pressing temperature is 160 to 170°C to make the two fit together to obtain a surface layer.

[0016] Description: PLON polylactic acid fibers are selected and opened into loose bundles, then combed into single fibers and arranged in a directional manner into a web. This process can arrange the fibers in an orderly manner to form a fiber web with a relatively uniform structure. Polylactic acid fibers have a certain softness and comfort, which can provide a comfortable surface touch for the fitted sheet. At the same time, the hot pressing process helps to form a relatively flat and smooth surface on the surface, which helps to improve the overall appearance and quality of the fitted sheet.

[0017] Furthermore, the method for making the edge is: select bamboo fiber and cotton fiber specifications that are the same as those of the hat surface, the blending ratio of bamboo fiber and cotton fiber is 2 to 3:7, the yarn twist coefficient is 340 to 360, and spun into 16-count yarn; the edge adopts a double-layer structure, the outer layer is a bamboo-cotton blended fabric, and the inner layer is a waterproof layer with a thickness of 0.1 to 0.3 mm, and the waterproof layer is made of polyester fiber.

[0018] Description: Controlling parameters such as the yarn twist factor helps to form a yarn with appropriate strength and flexibility, making the edging less likely to break or deform during daily use. The edging adopts a double-layer structure. The outer layer is a bamboo-cotton blended fabric, and the bamboo-cotton blend can bring the characteristics of bamboo fiber such as breathability and antibacterial properties, as well as the softness and comfort of cotton fiber. The inner layer is a polyester fiber waterproof layer. Controlling the thickness can effectively prevent moisture from penetrating into the inside of the edging, protecting the edging structure and the overall bed sheet, and will not make the edging too heavy to affect the overall aesthetics and use experience of the bed sheet. Moreover, polyester fiber has good durability, which can improve the wear resistance of the edging.

[0019] Further, the elastic anti-slip cloth adopts an interwoven fabric of spandex and nylon. The spandex content is 20-30%, and the nylon content is 70-80%.

[0020] Description: Spandex has the characteristic of high elasticity. At a content of 20-30%, it can provide good elasticity for the elastic anti-slip cloth, ensuring the fixing effect of the bed sheet. Nylon has high strength and wear resistance, ensuring that the elastic anti-slip cloth has sufficient strength to withstand daily friction and pulling, and guaranteeing its service life. When the two are interwoven together, it can not only give play to the elastic advantage of spandex, but also rely on the strength and wear resistance of nylon, so that the elastic anti-slip cloth can not only be firmly fixed on the mattress to play an anti-slip role, but also maintain good performance during long-term use and is not easily damaged.

[0021] Further, the cross-section of the elastic anti-slip cloth is in a square frame shape; on the surface of the elastic anti-slip cloth, raised rubber particles are evenly arranged by a hot pressing process. The diameter of the rubber particles is 0.5-1 mm, and the spacing between the rubber particles is 2-3 mm.

[0022] Description: The square frame shape can increase the surface area of contact between the elastic anti-slip cloth and the mattress, thereby enhancing the friction force and better preventing the bed sheet from sliding on the mattress; evenly arranging raised rubber particles with a diameter of 0.5-1 mm and a spacing of 2-3 mm on its surface by a hot pressing process further improves the anti-slip effect; these rubber particles increase the roughness of the surface of the elastic anti-slip cloth, and when contacting the surface of the mattress, more resistance contact points can be formed, increasing the friction force.

[0023] The beneficial effects of the present invention are:

[0024] In the present invention, through the blending of bamboo fiber and cotton fiber in the bamboo-cotton blended base layer, controlling the length and fineness of the bamboo fiber and the type of cotton fiber, it can not only give play to the antibacterial and breathable advantages of the bamboo fiber, but also rely on the cotton fiber to ensure softness, moisture absorption and strength; by treating the grey cloth with a nano-silver antibacterial finishing agent, using nano-silver with a specific particle size, controlling the agent concentration, padding rate and drying temperature, it can not only improve the antibacterial ability of the grey cloth, but also ensure the air permeability of the grey cloth without affecting the skin-friendly property of the surface layer of the bed sheet.

[0025] When preparing the middle layer, nanocellulose fibers and sodium carboxymethyl cellulose are dispersed in N,N-dimethylformamide, and PU resin is mixed with N,N-dimethylformamide in a certain proportion. Nanocellulose fibers have a unique physical structure, and their high aspect ratio and nanometer scale give them the ability to construct microscopic channels in the material. When they are dispersed in N,N-dimethylformamide, these fibers can form a network-like structure in the system of the middle layer. This network structure plays a role in regulating water vapor transmission at the microscopic level. Water vapor molecules can diffuse along the gaps between the nanocellulose fibers, thereby achieving a breathable effect. The thickness, temperature and vacuum degree of the coating on the base layer are appropriate, and the formed middle layer can enhance the structural stability, and has a positive effect on the waterproof, breathable, mildew-resistant and other properties of the mattress cover, so that the mattress cover has a variety of excellent properties as a whole. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 is a schematic diagram of the overall structure of Embodiment 1 of the present invention;

[0027] Figure 2 is a schematic structural diagram of the elastic anti-slip cloth of Example 1 of the present invention;

[0028] Figure 3 is a bar graph of hydrostatic pressure test of samples of Examples 1 to 11 of the present invention and Comparative Examples 1 to 6;

[0029] Figure 4 is a bar graph of air permeability test of samples of Examples 1 to 11 of the present invention and Comparative Examples 1 to 6;

[0030] Figure 5 is a bar graph of the antibacterial test of samples of Examples 1 to 11 of the present invention and Comparative Examples 1 to 6;

[0031] Among them, 1-hat surface, 2-edge, 3-elastic anti-slip fabric. DETAILED DESCRIPTION

[0032] In order to further illustrate the method adopted by the present invention and the effect achieved, the technical solution of the present invention will be clearly and completely described in combination with experiments below.

[0033] Embodiment 1:

[0034] A waterproof, breathable, mildew-resistant bamboo-cotton composite fabric mattress cover, such as Figures 1-2 As shown, the hat surface 1 includes a surrounding edge 2 connected to the hat surface 1, and an elastic anti-slip cloth 3 arranged at the bottom of the surrounding edge 2; the hat surface 1 includes a bamboo-cotton blended base layer, an intermediate layer arranged on the bamboo-cotton blended base layer, and a surface layer arranged on the intermediate layer;

[0035] The preparation method of the bamboo-cotton blended base layer is as follows: Select bamboo fibers and cotton fibers and blend them into a grey cloth according to a blending ratio of 3.5:6. Then immerse the grey cloth in a nano-silver antibacterial finishing agent with a concentration of 4 g / L, control the particle size of the nano-silver to be 33 - 36 nm, and then carry out padding and drying. The padding rate is 75%, and the drying temperature is 60 °C; the length of the bamboo fibers is 40 mm, and the fineness is 1.7 dtex; long-staple cotton is selected for the cotton fibers, the length of the cotton fibers is 337 mm, and the micronaire value is grade A, 3.7 - 4.2;

[0036] The preparation method of the intermediate layer is as follows: By mass percentage, disperse 2.75% of nano-cellulose fibers and 0.1% of sodium carboxymethyl cellulose in the remaining N,N-dimethylformamide, stir evenly to obtain a nano-cellulose fiber dispersion; at the same time, weigh another amount of N,N-dimethylformamide, and mix and dissolve PU resin and N,N-dimethylformamide in a mass ratio of 1:7 to obtain a PU resin solution; add the nano-cellulose fiber dispersion to the PU resin solution and stir and mix for 3 h. The mixing mass ratio of the nano-cellulose fiber dispersion and the PU resin solution is 1:4.5, and the stirring speed is 750 rpm to obtain a uniformly dispersed blend solution; then coat the blend solution on the bamboo-cotton blended base layer, with a coating thickness of 0.4 mm. At a temperature of 32.5 °C, control the vacuum degree to be 0.03 MPa until a film is formed after the solvent volatilizes to obtain the intermediate layer; the nano-cellulose fiber is CNF;

[0037] The preparation method of the surface layer is as follows: Select PLON polylactic acid fibers and loosen them into loose bundles, and then use a carding machine to card and loosen the fibers into single fibers and arrange them in a net in an oriented manner. Control the areal density to be 30 g / m 2 to obtain a fiber net. Lay the fiber net on the intermediate layer, and use a hot press to apply a pressure of 1.25 MPa to the fiber net for 20 s, and the hot pressing temperature is 165 °C to make the two fit together to obtain the surface layer;

[0038] The production method of the edge 2 is as follows: Select the same specifications of bamboo fibers and cotton fibers as those of the hat surface 1. The blending ratio of the bamboo fibers and the cotton fibers is 2.5:7, and the yarn twist coefficient is 350, and spin them into a 16-count yarn; the edge adopts a double-layer structure, the outer layer is a bamboo-cotton blended fabric, and the inner layer is a waterproof layer with a thickness of 0.2 mm. The waterproof layer uses polyester fibers;

[0039] The elastic anti-slip cloth 3 uses an interwoven fabric of spandex and nylon. The spandex content is 25%, the nylon content is 75%, and the cross-section of the elastic anti-slip cloth 3 is in a zigzag shape.

[0040] Embodiment 2: This embodiment is basically the same as Embodiment 1, except that, the preparation method of the bamboo-cotton blended base layer is as follows: bamboo fiber and cotton fiber are selected to be blended into a grey cloth according to a blending ratio of 3:6, and then the grey cloth is immersed in a nano-silver antibacterial finishing agent with a concentration of 3g / L, the particle size of the nano-silver is controlled at 20-25nm, and then the liquid is squeezed and dried, the liquid squeezing rate is 70%, and the drying temperature is 50°C; the length of the bamboo fiber is 38mm, and the fineness is 1.6dtex; the cotton fiber is long-staple cotton, and the cotton fiber length is 35mm.

[0041] Example 3: This example is basically the same as Example 1, except that the preparation method of the bamboo-cotton blended base layer is as follows: bamboo fiber and cotton fiber are selected to be blended into a grey cloth in a blending ratio of 4:6, and then the grey cloth is immersed in a nano-silver antibacterial finishing agent with a concentration of 5g / L, the particle size of the nano-silver is controlled at 45-50nm, and then the liquid is squeezed and dried, the liquid squeezing rate is 80%, and the drying temperature is 70°C; the length of the bamboo fiber is 42mm, and the fineness is 1.8dtex; the cotton fiber is long-staple cotton, and the cotton fiber length is 40mm.

[0042] Example 4: This example is basically the same as Example 1, except that, by mass percentage, 0.5% of nanocellulose fibers and 0.01% of sodium carboxymethyl cellulose are dispersed in the remaining amount of N,N-dimethylformamide and stirred evenly to obtain a nanocellulose fiber dispersion.

[0043] Example 5: This example is basically the same as Example 1, except that, by mass percentage, 5% of nanocellulose fibers and 0.2% of sodium carboxymethyl cellulose are dispersed in the remaining amount of N,N-dimethylformamide and stirred evenly to obtain a nanocellulose fiber dispersion.

[0044] Example 6: This example is basically the same as Example 1, except that PU resin and N,N-dimethylformamide are mixed and dissolved in a mass ratio of 1:4 to obtain a PU resin solution.

[0045] Example 7: This example is basically the same as Example 1, except that PU resin and N,N-dimethylformamide are mixed and dissolved in a mass ratio of 1:10 to obtain a PU resin solution.

[0046] Example 8: This example is basically the same as Example 1, except that the nanocellulose fiber dispersion is added to the PU resin solution and stirred for 2 hours, and the mixing mass ratio of the nanocellulose fiber dispersion and the PU resin solution is 1:3.

[0047] Example 9: This example is basically the same as Example 1, except that the nanocellulose fiber dispersion is added to the PU resin solution and stirred for 4 hours, and the mixing mass ratio of the nanocellulose fiber dispersion and the PU resin solution is 1:6.

[0048] Example 10: This example is basically the same as Example 1, except that the stirring speed is 500 rpm to obtain a uniformly dispersed blended solution; the blended solution is then coated on a bamboo-cotton blended base layer with a coating thickness of 0.05 mm. At a temperature of 25°C, the vacuum degree is controlled to be -0.05 MPa until the solvent evaporates and a film is formed to obtain an intermediate layer.

[0049] Example 11: This example is basically the same as Example 1, except that the stirring speed is 1000 rpm to obtain a uniformly dispersed blended solution; the blended solution is then coated on a bamboo-cotton blended base layer with a coating thickness of 0.1 mm. At a temperature of 40°C, the vacuum degree is controlled to be 0.1 MPa until the solvent evaporates and a film is formed to obtain an intermediate layer.

[0050] Example 12: This example is basically the same as Example 1, except that the nanocellulose fiber is CNC.

[0051] Example 13: This example is basically the same as Example 1, except that the nanocellulose fiber is BNC.

[0052] Example 14: This example is basically the same as Example 1, except that the surface layer is prepared by selecting PLON polylactic acid fibers and opening them into loose bundles, then using a carding machine to comb the opened fibers into single fibers and align them into a web, and adjusting the roller speed and gauge to control the surface density to 10 g / m 2 , obtain a fiber mesh, lay the fiber mesh on the middle layer, apply a pressure of 0.5 MPa to the fiber mesh for 10 seconds with a hot press machine, and the hot pressing temperature is 160°C to make the two fit together to obtain a surface layer.

[0053] Example 15: This example is basically the same as Example 1, except that the surface layer is prepared by selecting PLON polylactic acid fibers and opening them into loose bundles, then using a carding machine to comb the opened fibers into single fibers and oriented them into a web, and adjusting the roller speed and the gauge to control the surface density to 50 g / m 2 , obtain a fiber mesh, lay the fiber mesh on the middle layer, apply a pressure of 2MPa to the fiber mesh for 30s with a hot press machine, and the hot pressing temperature is 170°C to make the two fit together to obtain a surface layer.

[0054] Example 16: This example is basically the same as Example 1, except that the manufacturing method of the edge 2 is: selecting the same bamboo fiber and cotton fiber specifications as the hat cover 1, the blending ratio of the bamboo fiber and the cotton fiber is 2:7, the yarn twist coefficient is 340, and spun into 16-count yarn; the edge adopts a double-layer structure, the outer layer is a bamboo-cotton blended fabric, and the inner layer is a waterproof layer with a thickness of 0.1mm, and the waterproof layer is made of polyester fiber.

[0055] Example 17: This example is basically the same as Example 1, except that the manufacturing method of the edge 2 is: selecting the same bamboo fiber and cotton fiber specifications as the hat cover 1, the blending ratio of the bamboo fiber and the cotton fiber is 3:7, the yarn twist coefficient is 360, and spun into 16-count yarn; the edge adopts a double-layer structure, the outer layer is a bamboo-cotton blended fabric, and the inner layer is a waterproof layer with a thickness of 0.3mm, and the waterproof layer is made of polyester fiber.

[0056] Embodiment 18: This embodiment is basically the same as Embodiment 1, except that the elastic anti-slip cloth 3 is made of a woven fabric of spandex and nylon, the spandex content is 20%, and the nylon content is 70%.

[0057] Embodiment 19: This embodiment is basically the same as Embodiment 1, except that the elastic anti-slip cloth 3 is made of a woven fabric of spandex and nylon, the spandex content is 30%, and the nylon content is 80%.

[0058] Example 20: This example is basically the same as Example 1, except that the cross-section of the elastic anti-slip cloth 3 is in the shape of a U-shaped ...

[0059] Example 21: This example is basically the same as Example 1, except that the cross-section of the elastic anti-slip cloth 3 is in the shape of a U-shaped ...

[0060] Comparative Example 1: With reference to Example 1, 0.1% of nanocellulose fibers and 0.005% of sodium carboxymethyl cellulose were dispersed in the remaining amount of N,N-dimethylformamide by mass percentage, and stirred evenly to obtain a nanocellulose fiber dispersion.

[0061] Comparative Example 2: With reference to Example 1, PU resin and N,N-dimethylformamide were mixed and dissolved in a mass ratio of 1:12 to obtain a PU resin solution.

[0062] Comparative Example 3: With reference to Example 1, the nanocellulose fiber dispersion was added into the PU resin solution and stirred for 1 hour. The mixing mass ratio of the nanocellulose fiber dispersion and the PU resin solution was 1:2.

[0063] Control Example 4: Using Example 1 as a reference, the middle layer and the surface layer are not prepared, and the middle layer adopts a PU waterproof and breathable film, and the thickness of the film is controlled at 0.05 mm; the PU film is bonded to the upper surface of the bamboo-cotton blended base layer using hot melt adhesive bonding technology to ensure a firm and uniform bond without bubbles and wrinkles.

[0064] Control Example 5: Using Example 1 as a reference, the middle layer and the surface layer are not prepared, and the middle layer adopts a PU waterproof and breathable film, and the thickness of the film is controlled at 0.03 mm; the PU film is bonded to the upper surface of the bamboo-cotton blended base layer using hot melt adhesive bonding technology to ensure a firm and uniform bond without bubbles and wrinkles.

[0065] Control Example 6: Using Example 1 as a reference, the middle layer and the surface layer are not prepared, and the middle layer adopts a PU waterproof and breathable film, and the thickness of the film is controlled at 0.08 mm; the PU film is bonded to the upper surface of the bamboo-cotton blended base layer using hot melt adhesive bonding technology to ensure a firm and uniform bond without bubbles and wrinkles.

[0066] In order to explore the performance of the fitted sheet fabrics of some embodiments and control examples, the main materials were determined according to the experimental formula and samples were obtained for testing. The hydrostatic pressure test was performed according to the standard of GB / T4744-2013; the air permeability test was performed according to the standard of GB / T5453-1997; the antibacterial test of GB / T20944-2008 was performed using Escherichia coli, and the washing method of the washing color fastness tester was used to detect the antibacterial performance of the textile fabric after washing 10 times. The results are as follows: Figures 1 to 3 The specific research is as follows:

[0067] 1. Investigate the influence of the parameters of cotton blended base fabric preparation on the performance of the fitted sheet fabric:

[0068] like Figures 3 to 5 As shown, by comparing Examples 1 to 3, it can be seen that Example 1 has the highest hydrostatic pressure and the best air permeability, and its comprehensive performance is better; changing the raw material ratio parameters will have a certain impact on the prepared bed sheet fabric sample, and Example 2 has the lowest hydrostatic pressure; Example 3 has the best antibacterial performance, but the air permeability is slightly less than that of Example 1. It can be seen that the bed sheet fabric prepared using the process parameter values ​​of Example 1 has the best comprehensive performance.

[0069] 2. Explore the influence of the process parameters of the middle layer preparation on the performance of the fitted sheet fabric:

[0070] like Figures 3 to 5As shown, by comparing Examples 1, 4, 5 and Control Example 1, it can be seen that the hydrostatic pressure, air permeability and antibacterial performance of Example 4 are lower than those of Example 1, the hydrostatic pressure of Example 5 is higher than that of Example 4, and the air permeability of Example 4 is higher than that of Example 5. It can be seen that changing the ratio parameters of the nanocellulose fiber dispersion can have a certain effect on the performance of the fitted sheet fabric; compared with Control Example 1, the air permeability performance of Control Example 1 is much lower than that of Example 4, and the hydrostatic pressure and antibacterial performance are slightly higher than those of Example 1;

[0071] From the comparison between Examples 1, 6, 7 and Control Example 2, it can be seen that the hydrostatic pressure and antibacterial properties of Example 6 are slightly better than those of Example 1, but the difference is not obvious. The hydrostatic pressure and antibacterial properties of Example 7 are the lowest, and the air permeability is the highest. The air permeability of Example 6 is much lower than that of Examples 1 and 7. The comprehensive performance of Example 1 is the best. The bed sheet fabric prepared by the process parameter value closer to the ratio of the PU resin solution of Example 1 has the best comprehensive performance. The hydrostatic pressure and antibacterial properties of Control Example 2 are significantly lower than those of Example 7, and the air permeability is higher than that of Example 1.

[0072] From the comparison between Examples 1, 8, 9 and Control Example 3, it can be seen that the air permeability of Example 8 is better than that of Example 9, the hydrostatic pressure and antibacterial properties of Example 9 are better than those of Example 8, the hydrostatic pressure and antibacterial properties of Example 1 are slightly lower than those of Example 9, and the air permeability is higher than that of Example 9. Compared with the difference, Example 1 has the best comprehensive performance. The change of the mixing mass ratio of the plain fiber dispersion and the PU resin solution has a certain effect on the performance of the mattress cover fabric; the air permeability of Control Example 3 is higher than that of Example 1, and the hydrostatic pressure and antibacterial properties are much lower than those of Example 8;

[0073] By comparing Examples 1, 10, 11 and Control Examples 4 to 6, it can be seen that the air permeability of Example 11 is slightly better than that of Example 10, the hydrostatic pressure and antibacterial properties of Example 11 are slightly better than those of Example 10, and the various properties of Example 1 are the best. The change in the mixing mass ratio of the plain fiber dispersion and the PU resin solution has a certain effect on the performance of the fitted sheet fabric; the comprehensive performance of Control Example 4 is better than that of Control Example 5 and Control Example 7, the air permeability and antibacterial properties of Control Example 4 are much lower than those of Example 11, and the hydrostatic pressure is slightly lower than that of Example 11.

Claims

1. A waterproof, breathable, mildew-resistant bamboo-cotton composite fabric fitted sheet, characterized in that: It includes a hat surface (1), a border (2) connected to the periphery of the hat surface (1), and an elastic anti-slip cloth (3) provided at the bottom of the border (2); the hat surface (1) includes a bamboo-cotton blended base layer, an intermediate layer provided on the bamboo-cotton blended base layer, and a surface layer provided on the intermediate layer.

2. The waterproof, breathable, mildew-resistant bamboo-cotton composite fabric fitted sheet according to claim 1, characterized in that: The preparation method of the bamboo-cotton blended base layer is as follows: Select bamboo fibers and cotton fibers and blend them into a greige fabric according to a blending ratio of 3-4:

6. Then immerse the greige fabric in a nano-silver antibacterial finishing agent with a concentration of 3-5 g / L, control the particle size of nano-silver to be 20-50 nm, and then perform padding and drying. The padding rate is 70-80%, and the drying temperature is 50-70 °C; the length of the bamboo fibers is 38-42 mm, and the fineness is 1.6-1.8 dtex; long-staple cotton is selected for the cotton fibers, the length of the cotton fibers is 35-40 mm, and the micronaire value is 3.7-4.

2.

3. The waterproof, breathable, mildew-resistant bamboo-cotton composite fabric fitted sheet according to claim 1, characterized in that: The preparation method of the intermediate layer is as follows: By mass percentage, disperse 0.5-5% of nano-cellulose fibers and 0.01-0.2% of sodium carboxymethyl cellulose in the remaining N,N-dimethylformamide, stir evenly to obtain a nano-cellulose fiber dispersion; at the same time, weigh another portion of N,N-dimethylformamide, and mix and dissolve PU resin and N,N-dimethylformamide in a mass ratio of 1:4-10 to obtain a PU resin solution; add the nano-cellulose fiber dispersion to the PU resin solution and stir and mix for 2-4 h. The mixing mass ratio of the nano-cellulose fiber dispersion and the PU resin solution is 1:3-6, and the stirring speed is 500-1000 rpm to obtain a uniformly dispersed blend solution; then coat the blend solution on the bamboo-cotton blended base layer, with a coating thickness of 0.05-0.1 mm. At a temperature of 25-40 °C, control the vacuum degree to be -0.05-0.1 MPa until a film is formed after the solvent volatilizes to obtain the intermediate layer.

4. The waterproof, breathable, mildew-resistant bamboo-cotton composite fabric fitted sheet according to claim 3, characterized in that: The nano-cellulose fiber is one of CNF, CNC, and BNC.

5. The waterproof, breathable, mildew-resistant bamboo-cotton composite fabric fitted sheet according to claim 1, characterized in that: The preparation method of the surface layer is as follows: PLON polylactic acid fibers are selected and opened into loose bundles, and then the opened fibers are combed into single fibers by a carding machine and arranged in a directional manner into a web, and the surface density is controlled to be 10-50 g / m by adjusting the roller speed and the gauge. 2 , obtain a fiber mesh, lay the fiber mesh on the middle layer, apply a pressure of 0.5 to 2 MPa to the fiber mesh for 10 to 30 seconds using a hot press machine, and the hot pressing temperature is 160 to 170°C to make the two fit together to obtain a surface layer.

6. The waterproof, breathable, mildew-resistant bamboo-cotton composite fabric fitted sheet according to claim 2, characterized in that: The production method of the border (2) is as follows: Select the same specifications of bamboo fibers and cotton fibers as those of the hat surface (1). The blending ratio of the bamboo fibers and cotton fibers is 2-3:7, and the yarn twist coefficient is 340-360 to spin a 16-count yarn; the border adopts a double-layer structure, the outer layer is a bamboo-cotton blended fabric, and the inner layer is a waterproof layer with a thickness of 0.1-0.3 mm. The waterproof layer uses polyester fiber.

7. The waterproof, breathable, mildew-resistant bamboo-cotton composite fabric fitted sheet according to claim 1, characterized in that: The elastic anti-slip cloth (3) uses an interwoven fabric of spandex and nylon. The spandex content is 20-30%, and the nylon content is 70-80%.

8. The waterproof, breathable, mildew-resistant bamboo-cotton composite fabric fitted sheet according to claim 1, characterized in that: The cross-section of the elastic anti-slip cloth (3) is in a zigzag shape; on the surface of the elastic anti-slip cloth (3), convex rubber particles are uniformly arranged by a hot pressing process. The diameter of the rubber particles is 0.5-1 mm, and the spacing between the rubber particles is 2-3 mm.